Zoonotic gastrointestinal nematodes in pet cats in Yogyakarta (Indonesia) and their susceptibility to anthelmintics - IRKHAM WIDIYONO; RUSMIHAYATI RUSMIHAYATI; HARY PURNAMANINGSIH; ANA SAHARA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Widiyono I, Rusmihayati, Purnamaningsih H, Sahara A. 2023. Zoonotic gastrointestinal nematodes in pet cats in Yogyakarta (Indonesia) and their susceptibility to anthelmintics. Biodiversitas 24: 3332-3337. Domestic cats (Felis catus Linnaeus, 1758), which live close to humans, can host some zoonotic nematodes. Therefore, a study on gastrointestinal nematodes in domestic cats and their anthelmintic resistance is essential for controlling and preventing zoonotic nematodiasis. Our goal was to investigate the diversity of gastrointestinal nematodes in pet cats in Yogyakarta and their susceptibility to anthelmintics. One hundred seventy-four (174) out of 215 cat patients (80.93%) presented at the animal clinic of the Department of Internal Medicine, Faculty of Veterinary Medicine, Universitas Gadjah Mada, Yogyakarta, Indonesia, and suspected gastrointestinal parasite infections suffered from nematodiasis. Ninety-eight (98) animals suffering from moderate to severe gastrointestinal nematodiasis with Egg Per Gram feces (EPG) >300 were included into nematode identification, clinical analyses, and evaluation of nematode susceptibility to anthelmintics. The animals were divided in three treatment groups, namely pyrantel pamoate at the dose of 5 mg/kg BW orally on D0 (OP), subcutaneous injection of ivermectin at the dose of 200 µg/kg BW on day 0 (SCI), and no medication as a Control (C). Fecal samples were collected on day 0 and 10 for parasitological examinations. The results showed that pet cats were infected with Toxocara sp. and Ancylostoma sp., with the incidence of single infection by Toxocara sp., Ancylostoma sp., and mixed infection at 50%, 36.73%, and 13.27%, respectively. The animals were clinically healthy or showing clinical signs, e.g., anorexia, diarrhea, vomiting, and dull hair. Pyrantel pamoate and ivermectin showed >98% efficacy against these nematodes. In conclusion, there were two zoonotic gastrointestinal nematodes in pet cats in Yogyakarta, namely Ancylostoma and Toxocara, which still showed high susceptibility to pyrantel pamoate and ivermectin.